Integrating Network Pharmacology and in vivo Validation to Explore the Mechanisms of Buyang Huanwu Decoction in Myocardial Ischemia-Reperfusion Injury - Luo Y; Hu W; Li Z; Zhang X; Chen S; Yang Q; Hu B; Zou X (Journal of Inflammation Research)
Yushan Luo,1 Wen Hu,1 Ziyue Li,1 Xiaoyuan Zhang,1 Shoujun Chen,1 Qiang Yang,1 Bailong Hu,2 Xiaohua Zou2 1Guizhou Medical University, Guiyang, Guizhou, 550004, People’s Republic of China; 2Department of Anesthesiology, The Affiliated Hospital of Guizhou Medical University, Guiyang, Guizhou, 550004, People’s Republic of ChinaCorrespondence: Bailong Hu, Department of Anesthesiology, Affiliated Hospital of Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China, Tel +86-15185184309, Email hubailong@gmc.edu.cn Xiaohua Zou, Department of Anesthesiology, Affiliated Hospital of Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China, Tel +86-13809416036, Fax +86-851-86771013, Email zouxiaohuazxh@sina.comObjective: Buyang Huanwu Decoction (BYHWD), a traditional Chinese herbal formula, has been widely used to manage cardiovascular disorders. However, its cardioprotective mechanisms in myocardial ischemia/reperfusion injury (MI/RI) remain unclear. This study aims to investigate its pharmacological mechanisms against MI/RI through network pharmacology and experimental validation.Materials and Methods: Active components and targets of BYHWD were identified via Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform, Encyclopedia of Traditional Chinese Medicine, BATMAN-TCM, and SymMap databases. MI/RI-related targets were retrieved from DisGeNET, GeneCard, Online Mendelian Inheritance in Man, Comparative Toxicogenomics Database, and DrugBank databases. The intersecting targets were analyzed using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment. Protein-protein interaction (PPI) networks, compound-target networks, and herb-target-pathway networks were constructed using Cytoscape, and molecular docking was performed via AutoDock Vina. A rat MI/RI model was used to assess infarct size, protein expression, and cytokine levels for in vivo validation.Results: 95 compounds were identified, with 75 MI/RI-related targets. PPI analyses highlighted ten hub genes, including interleukin-6 (IL6), AKT serine/threonine kinase 1 (AKT1), tumor necrosis factor (TNF), intercellular adhesion molecule 1 (ICAM1), matrix metalloproteinase 9 (MMP9), interleukin-10 (IL10), vascular cell adhesion molecule 1 (VCAM1), nitric oxide synthase 3, albumin, and C-reactive protein. GO and KEGG analyses highlighted TNF signaling, apoptosis, and p53 signaling pathways. Carthami Flos and Radix Astragali emerged as core herbs, with quercetin, kaempferol, baicalein, stigmasterol, baicalin, and beta-sitosterol as key compounds exhibiting strong binding affinities to hub genes. In vivo, BYHWD significantly reduced myocardial infarct size, decreased inflammatory cytokines (IL6 and TNF-α), ICAM1, VCAM1, and MMP9 protein expression, and IL10 and phosphorylated AKT1 expression.Conclusion: BYHWD alleviates MI/RI through multicomponent, multitarget, and multipathway mechanisms, primarily modulating TNF and AKT1-mediated inflammatory/apoptotic pathways. These effects collectively support its potential as a complementary treatment for ischemic heart disease.Keywords: Buyang Huanwu decoction, myocardial ischemia reperfusion injury, network pharmacology